(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This in the article school age in children main problem has been knowledge efficiency decline , memory weakness , attention and of attention decrease such as problems " to the Internet of the disease of addiction reason what is happening , him cause issuing factors and them eliminate reach ways about about thought and considerations father of mothers their children from the internet to their use has been relations and control given